2011
DOI: 10.1111/j.1582-4934.2009.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin A-β is required for hypertrophy but not matrix expansion in the diabetic kidney

Abstract: Calcineurin is an important signalling protein that regulates a number of molecular and cellular processes. Previously, we found that inhibition of calcineurin with cyclosporine reduced renal hypertrophy and blocked glomerular matrix expansion in the diabetic kidney. Isoforms of the catalytic subunit of calcineurin are reported to have tissue specific expression and functions. In particular, the β isoform has been implicated in cardiac and skeletal muscle hypertrophy. Therefore, we examined the role of calcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Our results are in line with previous studies, showing that the inhibition of calcineurin reduced renal hypertrophy and blocked glomerular hypertrophy in kidneys from diabetic rats [31]. In addition, whole kidney and glomerular hypertrophy were also reduced in diabetic calcineurin A-β knockout mice [32]. It may be concluded that the insulin-TRPC6-calcium/calmodulin-calcineurin-nuclear factor of activated T cells-pathway may be important for the pathogenesis of diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are in line with previous studies, showing that the inhibition of calcineurin reduced renal hypertrophy and blocked glomerular hypertrophy in kidneys from diabetic rats [31]. In addition, whole kidney and glomerular hypertrophy were also reduced in diabetic calcineurin A-β knockout mice [32]. It may be concluded that the insulin-TRPC6-calcium/calmodulin-calcineurin-nuclear factor of activated T cells-pathway may be important for the pathogenesis of diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, Wada et al (43) reported that overexpression of constitutively active CnA␣ did not increase miR-23a expression. Since we and others (14,33) reported that NFAT is regulated by CnA␤, the other CnA catalytic subunit isoform in skeletal muscle, we overexpressed a constitutively active form of CnA␤ by adenoviral infection (CnA␤ AV) in C2C12 cells to test how it affected miR-23a. Similar to the findings of Wada et al, CnA␤ AV did not increase the level of miR-23a; however, it did prevent the Dex-induced suppression of miR-23a (Fig.…”
Section: Mir-23a and Cn/nfat Signaling Are Suppressed During Muscle Amentioning
confidence: 99%
“…CaNA-a was the predominant isoform expressed in the proximal tubules and was associated with ECM synthesis and TGF-b expression, 26,27 whereas the b-isoform was expressed mostly in glomeruli. Gooch et al 26 found that rats lacking a-isoform displayed renal developmental defects or fibrosis, which coincided with the side effects of CsA.…”
Section: Effects Of Can Sirna On Can Mrna and Protein Expression Of Hmentioning
confidence: 99%